Reflection and Analysis on the Construction of a High-Quality Employment Evaluation System for Chinese Medical Students - Yanfei, Zheng; Xiaoshang, Wang; Xuebo, Zhu (International Journal of Educational Studies, 2025)
Against the backdrop of the transformation in the medical industry driven by new-quality productivity, high-quality employment formedical students is confronted with challenges such as the transformation of skill structures and the imbalance between supply and demand.This paper constructs an evaluation framework from four dimensions:personal qualities, educational training,market demand,and policy support.By integrating the latest trends,including grassroots medical policies,academic competitiveness,core indicators of employment quality,and career planning pathways,the analysis identifies new-quality productivity-oriented core employment elements such as digitalization of clinical capabilities, innovative scientific research thinking,and adaptability to grassroots services.The paper proposes a "three-dimensional synergy" response strategy, encompassing the reshaping of individual competitiveness,the reconstruction of the educational system, and the innovation of policy-market linkage mechanisms, providing theoretical support and practical pathways for resolving the structural contradictions in medical students’employment.